Asymptotic safety and Kaluza-Klein gravitons at the LHC - Gerwick, Erik; Litim, Daniel F.; Plehn, Tilman (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
We study Drell-Yan production at the LHC in low-scale quantum gravity models with extra dimensions. Asymptotic safety implies that the ultraviolet behavior of gravity is dictated by a fixed point. We show how the energy dependence of Newton’s coupling regularizes the gravitational amplitude using a renormalization group improvement. We study LHC predictions and find that Kaluza-Klein graviton signals are well above standard model backgrounds. This leaves a significant sensitivity to the energy scale ΛT where the gravitational couplings crossover from classical to fixed point scaling.
Gesehen am 09.11.2023